Missionary Architecture and Hybrid Modernity in Colonial Korea: The Case of Yonsei University. Issue 4 (1st December 2017) - Paek, Seunghan; An, Dai Whan
Abstract : This article explores the hybrid modernity made through missionary architectural practices during colonial Korea, by examining how the master plan of Yonsei University, one of the earliest mission schools in Korea, has gone through a unique evolutionary process throughout the convoluted modern history of the twentieth century. In doing so, this article conducts a thorough visual and spatial analysis of the given case with two emphases: first, analyzing three campus master plans—produced in 1917, 1925, and 2016 respectively—in a comparative way; and second, analyzing the layout and façade composition of major buildings that comprise the campus in great details. These master plans are crucial evidences enabling us to investigate the transatlantic architectural practices in early 20th century, as Henry K. Murphy, the architect in charge of the first two master plans of Yonsei University, was one who had long practiced in New York and greatly admired the values of Asian architecture through a series of field trips to major Asian cities, including Beijing, Shanghai, Tokyo, and Seoul. While the 1917 master plan was in part influenced by the Western precedents, as well as ones from Japan and China some of which Murphy himself was involved in as a master architect the 1925 case deviates from it and illustrates multiple points of transformation that go beyond spatial symmetry and visual harmony. The 1925 one is marked by the rearranged spatial disposition and façade composition of dormitories and residential halls as influenced by the geographical peculiarities of Korea at that time. Long after the revision, the third, 2016, version illustrates the much expanded, triangular shape toward the south with added buildings and facilities, while the entombment area and other historical fragments in the upper part are well preserved. Hence, this article claims that the case of Yonsei University elicits the hybridization of missionary architectural practices and local Korean culture throughout the twentieth century, which is neither subsumed by the missionaries' imposition of design ideas nor bound by the authentically Korean tradition of design.